Transcarotid Approach to Placement of an Impella 5.0. Issue 1 (17th March 2021) - Ramamurthi, Adhitya; Cain, Michael T.; Smith, Nathan; Espinal, Angelia; Joyce, David L.; Mohammed, Asim; Joyce, Lyle D.; Durham, Lucian A.
Abstract : Microaxial left ventricular assist devices (mLVADs) have traditionally been placed through a transfemoral or transaxillary arterial approach. Transfemoral access is restrictive, significantly limiting postoperative patient ambulation. Transaxillary placement is preferred but not feasible in a subset of patients due to small arterial diameter or tight angulation of the thoracic outlet. Transcarotid delivery has been utilized for other cardiovascular device deployment with good success; however, this approach has not been described for mLVAD support. We present a case series of transcarotid placement of mLVADs in cases where a transaxillary and transfemoral approach was not feasible. From May 2017 to April 2019, six patients in cardiogenic shock required mLVAD support achieved via a transcarotid approach. Technical success was achieved in all patients. One patient was directly weaned from mLVAD support and two patients died on mLVAD support. Escalation to venoarterial extracorporeal membrane oxygenation (VA-ECMO) was required for three patients, two of whom subsequently died. There were no bleeding or valvular complications related to device placement, and no obvious or known neurologic complications related to mLVAD support. Transcarotid placement of mLVADs expands the utility of these devices as an alternative to traditional support strategies or prohibitive arterial anatomy; however, further study is needed to determine its efficacy.